Effects of Adolescents’ Lifestyle Habits and Body Composition on Bone Mineral Density - Han, Chang-Sook (Int J Environ Res Public Health, 2021)
The incidence of osteoporosis is increasing as the population ages, as is the need to manage and prevent it. Adolescence is the period when the fastest development of bone mass takes place. Increasing adolescents’ maximum bone mass and avoiding the risk factors for its loss are effective for preventing osteoporosis. This study investigated the factors influencing adolescents’ bone mineral density (BMD). The participants were 126 middle- and high-school students from Gangwon-do; 47.6% (n = 60) were male, with an average age of 15 (range 12–18) years of age. It was found that age, carbonated beverages, snacks, and calcium supplements were variables that showed significant differences in adolescents’ BMD. Additionally, through correlation analysis, it was found that height, weight, body mass index (BMI), body water, protein, minerals, body fat mass, and skeletal muscle mass were correlated with BMD. Multiple regression analysis identified age, calcium supplements, BMI, body fat mass, and skeletal muscle mass as BMD-associated factors. These results show that adolescents’ BMD is higher with lower body fat mass, higher BMI and skeletal muscle mass, and a higher intake of calcium supplements.